(untitled) (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: This study aimed to describe the results of applying silver dressing on diabetic ulcers during infection in patients with infected wounds on digiti one pedis dextra. Methods: This research uses a descriptive design, namely a case study with a nursing approach consisting of assessment, analysis of problem formulation, formulation of nursing diagnosis, intervention, implementation, evaluation, and nursing documentation. The subject of this case study is Mrs. A with diabetic ulcers on Digi 1 pedis extra with infection. Case management was carried out for three days on April 17-19, 2024. Data was collected through anamnesis, wound assessment, supporting examination, and literature study. Wound assessment was performed using the Meggitt-Wagner instrument for assessing wound severity and the SINBAD (Site, Ischemia, Neuropathy, Bacterial infection, Area ulcer, and Depth) system for improving foot ulcer management according to their severity and predicting major adverse foot events. Results: After three days of treatment using silver dressing, the wound condition shows that the infection has been resolved, and the wound has improved significantly from a grade 2 diabetic ulcer with abscess using the Meggitt-Wagner instrument and a SINBAD score of 3 (less severe ulcer) to a grade 2 diabetic ulcer without abscess and a SINBAD score of 2 (less severe ulcer). Conclusion: Wound care using silver dressing significantly accelerates the resolution of infections and supports the overall healing process